Kindred in death - Robb, J. D., frey50 (Detroit : Gale, 2010)
Investigating the brutal murder of her new captain's sixteen-year-old daughter, Lieutenant Eve Dallas believes she is closing in on the perpetrator only to encounter a series of teasing clues that suggest the identities of several possible suspects.
Originally published: New York : G.P. Putnam's Sons, 2009.
Keywords: Dallas, Eve (Fictitious character); Policewomen; Children of police -- Crimes against; Teenage girls -- Crimes against; New York (N.Y.); Large type books; Mystery fiction